Understanding the Old Testament - Williams, Jay G., 1932- (New York : Barron's Educational Series, inc., 1972)
Begrijp het Oude Testament beter dank zij dit boek.
Bibliography: p. 331-340.
Keywords: Bible. -- Introductions